Lean evolution : lessons from the workplace - Rich, Nick (Cambridge University Press, 2006)
Lean thinking is a powerful method that allows organizations to improve the productivity, efficiency, and quality of their products or services. This book shows how it can be applied in practice, highlighting the key challenges. For managers at all levels, as well as business students and researchers in lean thinking.